HUBUNGAN DURASI DENGAN KONSENTRASI BELAJAR MAHASISWA PSSKPPN FK UNUD SELAMA PEMBELAJARAN DARING - Widhi, Rai Sekar; Saputra, I Kadek; Juniartha, I Gusti Ngurah (Coping: Community of Publishing in Nursing; Vol 11 No 4 (2023): Agustus 2023DO - 10.24843/coping.2023.v11.i04.p05, 2023)
Online learning makes the process, time and method for learning more flexible for students and lecturers. However, several obstacles experienced by students were identified such as boredom and fatigue caused by staring at the screen for too long during online learning and it could disrupts their learning concentration. Learning concentration is very important to support student success during the learning process which will have an impact on student academic achievement. This research aims to describe the correlation between duration and learning concentration in students of the Bachelor of Nursing and Professional Nursing Study Program Faculty Of Medicine Udayana University during online learning. The type of research used is quantitative research with a cross-sectional research design. This study used probability sampling type proportionate stratified random sampling with a sample of 176 people. The results of this study show that the average duration of online learning is 249 minutes a day and the average of student learning concentration is 101,74 which is included in the moderate learning concentration. The results of the Spearman Rank correlation test in this study showed a p value = 0,874 > 0,05 which means there is no significant correlation between the duration and learning concentration in students of the Bachelor of Nursing and Professional Nursing Study Program Faculty Of Medicine Udayana University during online learning.